Development of IoT-based footwork ability test using ESP32 camera for badminton athletes - Setiawan, Moza Zeane; Williyanto, Septian; Subarjah, Herman; Fitri, Mustika (Jorpres (Jurnal Olahraga Prestasi), 2024)
Badminton requires open and fast movements towards the shuttlecock, but there is no specific agility test for badminton players with specific movements to assess the athlete's footwork ability. This leads to a lack of objective indicators to know the progress of the results of the exercises. Researchers aim to produce useful technology to measure the agility of badminton athletes as a tool of Footwork Test and Training. The method used is Research & Development (R&D). The test involved 26 badminton athletes in Bandung. After going through the validity test by experts (expert judgment) shows that the validation technology performed by 3 validators get a value of 95% can be categorized as very good. The accuracy of the score calculation system of 99.96% is in the very high category. The results showed that footwork ability test technology received a positive response from athletes and coaches, this tool can also serve as a trainer tool to guide athletes in carrying out footwork exercises. Thus, footwork ability test technology has been declared worthy of use as a medium of tests and exercises.